PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA UD. KENCANA LESTARI DENPASAR - Sapta Rini Widyawati; Putu Agus Eka Rismawan; Irene Novita Sofia Ina Kii (VALUES, 2024)
Employee performance is a work result achieved by a person in carrying out the tasks assigned to him which is based on skill, experience, seriousness and time. There is a decline in employee performance because one of the leadership functions in terms of evaluation is not carried out well, the work environment is less supportive and high work stress. This research aims to determine the influence of leadership, work environment and work stress on the performance of UD employees. Kencana Lestari Denpasar. The population in this study were all UD employees. Kencana Lestari Denpasar numbers 40 people. The sample was determined using a saturated sampling technique with a sample size of 40 people. The data collection methods used were observation, interviews and questionnaires. The data analysis techniques used are descriptive analysis, classical assumption test, multiple linear regression analysis, multiple correlation analysis, determination analysis and t test. The test results show that leadership has a positive and significant effect on employee performance at UD. Kencana Lestari Denpasar. The work environment has a positive and significant effect on employee performance at UD. Kencana Lestari Denpasar. Job Stress has a negative and significant effect on employee performance at UD. Kencana Lestari Denpasar.